Mucosal SIV Vaccines Comprising Inactivated Virus Particles and Bacterial Adjuvants Induce CD8+ T-Regulatory Cells that Suppress SIV-Positive CD4+ T-Cell Activation and Prevent SIV Infection in the Macaque Model - Andrieu, Jean-Marie; Chen, Song; Lai, Chunhui; Guo, Weizhong; Lu, Wei (Frontiers in Immunology, 2014)
A new paradigm of mucosal vaccination against HIV infection has been investigated in the macaque model. A vaccine consisting of inactivated SIVmac239 particles together with a living bacterial adjuvant (either the Calmette & Guerin bacillus, lactobacillus plantarum or Lactobacillus rhamnosus) was administered to macaques via the vaginal or oral/intragastic route. In contrast to all established human and veterinary vaccines, these three vaccine regimens did not elicit SIV-specific antibodies nor cytotoxic T-lymphocytes but induced a previously unrecognized population of non-cytolytic MHCIb/E-restricted CD8+T regulatory cells that suppressed the activation of SIV positive CD4+ T-lymphocytes. SIV reverse transcription was thereby blocked in inactivated CD4+ T-cells; the initial burst of virus replication was prevented and the vaccinated macaques were protected from a challenge infection. Three to 14 months after intragastric immunization, 24 macaques were challenged intrarectally with a high dose of SIVmac239 or with the heterologous strain SIV B670 (both strains grown on macaques PBMC). Twenty-three of these animals were found to be protected for up to 48 months while all 24 control macaques became infected. This protective effect against SIV challenge together with the concomitant identification of a robust ex-vivo correlate of protection suggests a new approach for developing an HIV vaccine in humans. The induction of this new class of CD8+ T regulatory cells could also possibly be used therapeutically for suppressing HIV replication in infected patients and this novel tolerogenic vaccine paradigm may have potential applications for treating a wide range of immune disorders and is likely to may have profound implications across immunology generally.